Does physical activity affect the pain and mobility of the lumbosacral spine in pregnant women? - case-control study - Anna Ziółkowska; Paweł Wojtczak; Wiktoria Śniegowska; Dominika Ciecierska; Edyta Piechocka; Bartłomiej Wrzesiński; Maciej Dzierżanowski; Urszula Kazimierczak (Kazimierz Wielki University, 2018)
Background: Daily physical training is safe and brings many benefits to pregnant woman. When there are no contraindications, regular exercise of gymnastics has a positive effect on the overall physical fitness, well-being of the woman. In addition it reduces the symptoms of typical pregnancy. Material and methods: The study involved pregnant women who were in the second or third trimester during the study. The study group consisted of 45 healthy pregnant women (n=45). During the research, range of motion and the shape of the curvature of the lumbar spine using the CMS10 Zebris device was performed. Additionally, the author's questionnaire was also used, which allowed to gather important information about the practiced physical activity in the pregnancy of the surveyed women and check the knowledge about physical activity during pregnancy. The questionnaire was also used to gather basic information such as age, weight, height or education. Results: In the examined group of pregnant women the mean flexion of the lumbar spine to the front was 54.5⁰, to the back 16⁰, to the left 23⁰ and to the right 24.5⁰. The average spine turn to the left is 16.5⁰ and to the right 15.5⁰. 100% of the surveyed women, responded that physical activity during pregnancy is recommended, 82.22% of them are active during pregnancy. The most common physical activities are walking, next is swimming and special exercises for pregnant women and yoga. The fewest group were the women exercising Pilates. 31.11% of women exercise three times a week, 37.78% - twice a week, 22.22% - one a week and 6.67% less than one a week. 64.44% of women feel good thanks to practiced physical activity, 31.11% of women say that exercises improve their wellbeing. Conclusions: Regular physical activity has a positive impact on the wellbeing of women which participated in the research. Women's knowledge about physical activity during pregnancy is quite high although it does not always translate to real world performed exercises. The study did not show the impact of physical activity on the mobility of the lumbar spine, but the study should be continued at a larger study group.